Exploring the Impact of Family Socio-Economic Status on Children’s Bilingual Abilities Among Arab Families - Ahmed Mohamed; Qiuzhi Xie; Maxwell Peprah Opoku; Aisha Cheikhmous (Education Sciences)
This study investigates the impact of family socio-economic status on children’s bilingual oral language and reading abilities. The participants were 92 Arabic–English bilingual children (Meanage = 8.52 years old) in Grade 3 of primary schools and their parents in the United Arab Emirates. A correlational research design was used. The children completed several bilingual oral language and reading tests, and their parents filled in the family background questionnaire. The results of general regression show that mothers’ education level and family income affected children’s English, but not Arabic, oral language and word reading abilities. Family income was a significant predictor of children’s English oral language skills, and mothers’ education level contributed to children’s English word reading. However, fathers’ education level did not predict children’s bilingual abilities. The contextual influence on children’s language and literacy development is discussed.